Love of Reading Meets PISA Assessments: Historical Insights in the Discourse on Reading Motivation - Mäkinen, Ilkka (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian] One of the most notable phenomena during the last two decades in the educational field has been the global shock wave sent all over the world by the PISA assessments. As if by chance it was detected that competence in reading is dependent on reading motivation. Fluent reading requires practice, i.e., a sufficient number of pages read and hours spent in reading, which requires an intrinsic motivation to read in the person who reads. To a certain extent, one has to love reading. This article seeks to study how the role of the reading motivation, or love of reading, was detected, where the necessary theoretical and methodological knowhow was found, and how the whole process revives an age-old rhetorical tradition in the discourse on reading.